The Improvement of Protein Retention through a Higher Utilization of Carbohydrate in the Diet with Chromium for Common Carp Cyprinus carpio Linn. - Nuryati S; D. Dana; M.B. Malole; F.H. Pasaribu (Jurnal Akuakultur Indonesia)
Primary shrimp cell culture from lymphoid organ of Penaeus monodon was successfully developed. Minced tissues of lymphoid organ were seeded by tripsin enzyme and culture in Leibovit'z-15 supplemented with 10% fetal bovine serum and 5% NaCl. Plates were then incubated at 27 °C with 5% C02 supply. Confluent cells were infected by white spot baculovirus (WSBV). Cytopathic effect (CPE) induced by white spot baculovirus showed characteristics of detachment cells and lysis forming giant polycaryon cells. Primary shrimp cell culture could be continued by anvanced cell culture resulting cell line could be used virus media.